THE IMPACT OF GOVERNMENT AGRICULTURAL EXPENDITURE ON POVERTY IN ZIMBABWE - A. Mapfumo; A. Mushunje; C. Chidoko (Russian Journal of Agricultural and Socio-Economic Sciences, 2012)
Global experience with pro-poor growth and empirical work spanning India, Benin and Malawi demonstrates the importance of agricultural expenditure for poverty reduction in poor rural areas, while also pointing to the need for complementary non farm sector growth. This paper proposes a simple methodology to estimate the agricultural spending that will be required to achieve the Millennium Development Goal of halving poverty by 2015 (MDGs) in Zimbabwe. This method uses growth poverty and growth expenditure elasticities to estimate the financial resources required to meet the MDGs. The paper attempts to address a key knowledge gap by improving estimation of first MDG agricultural expenditure at country level.